Electronic Properties of CdTe/CdS Solar Cells as Influenced by a Buffer Layer. Issue 14 (2016) - Fedorenko, Y. G.; Major, J. D.; Pressman, A.; Phillips, L.; Durose, K.
ABSTRACT: We considered modification of the defect density of states in CdTe as influenced by a buffer layer in ZnO(ZnS, SnSe)/CdS/CdTe solar cells. Compared to the solar cells employing ZnO buffer layers, implementation of ZnSe and ZnS resulted in the lower net ionized acceptor concentration and the energy shift of the dominant deep trap levels to the midgap of CdTe. The results clearly indicated that the same defect was responsible for the inefficient doping and the formation of recombination centers in CdTe. This observation can be explained taking into account the effect of strain on the electronic properties of the grain boundary interface states in polycrystalline CdTe. In the conditions of strain, interaction of chlorine with the grain boundary point defects can be altered.